Situating biologies of traditional Chinese medicine in Central Europe - Stöckelová, Tereza; Trnka, Susanna (Anthropology & medicine, 2020)
Since the concept of 'local biologies' was proposed in the 1990s, it has been used to examine biosocial processes that transform human bodies in similar and different ways around the globe. This paper explores understandings of biosocial differentiation and convergence in the case of Traditional Chinese Medicine (TCM) in the Czech Republic. Specifically, it examines how Czech TCM practitioners view TCM as universally applicable while fine-tuning it to situated biosocial conditions, experimenting with the compatibilities of various human and plant bodies as part of their generalised, clinical practice. Drawing upon ethnographic research among TCM practitioners in the Czech Republic, it suggests that in addition to the individualization of TCM therapeutics to suit particular patients, Czech TCM is characterised by collective particularization, shaped by local concerns over ethnic, environmental and cultural differences. By looking critically at TCM practitioners' sensitivities to localised biological similarities and differences it aims to contribute to understandings of the expansion of TCM in Central Europe, as well as more broadly to current social science debates over the risks and opportunities inherent in abandoning the assumption of a universal human body and biology.
Keywords: Anthropology, Medical; Local biologies; Medicine, Chinese Traditional; Traditional Chinese Medicine (TCM); poskytování zdravotní péče; globalisation; Humans; tradiční čínská medicína; situated biologies; Czech Republic; lékařská antropologie; lidé; Delivery of Health Care; Česká republika